Expression Levels of PIWI-interacting RNA, piR-823, Are Deregulated in Tumor Tissue, Blood Serum and Urine of Patients with Renal Cell Carcinoma - Iliev, Robert; Fedorko, Michal; Machackova, Tana; Mlcochova, Hana; Svoboda, Marek; Pacik, Dalibor; Dolezel, Jan; Stanik, Michal; Slaby, Ondrej (Anticancer research, 2016)
BACKGROUND: Renal cell carcinoma (RCC) is the most common neoplasm of adult kidney accounting for about 3% of adult malignancies. P-Element induced wimpy testis (PIWI)-interacting RNAs (piRNAs) are a new class of naturally occurring, short non-coding RNAs involved in silencing of transposable elements and in sequence-specific chromatin modifications. There were preliminary data published indicating that piR-823 expression is deregulated in circulating tumor cells and tumor tissue in gastric and kidney cancer, respectively. PATIENTS AND METHODS: In our study, we analyzed piR-823 levels in 588 biological specimens: tumor tissue (N=153), adjacent renal parenchyma (N=121), blood serum (N=178) and urine (N=20) of patients undergoing nephrectomy for RCC; and in blood serum (N=101) and urine (N=15) of matched healthy controls. Expression levels of piR-823 were determined in all biological specimens by quantitative real-time polymerase chain reaction, compared in patients and controls, and correlated with clinicopathological features of RCC. RESULTS: We identified a significant down-regulation of piR-823 in tumor tissue [p<0.0001, area under the curve (AUC)=0.7945]. On the contrary in blood serum and urine, the expression of piR-823 was significantly higher in patients with RCC compared to healthy individuals (p=0.0005, AUC=0.6264 and p=0.0157, AUC=0.7433, respectively). We further observed higher levels of piR-823 in tumor tissue to be associated with shorter disease-free survival of patients (p=0.0186) and a trend for higher piR-823 levels in serum to be associated with advanced clinical stages of RCC (p=0.0691). There were no other significant associations of piR-823 levels in any type of biological specimen with clinicopathological features of RCC. CONCLUSION: piR-823 is down-regulated in tumor tissue, but positively correlated with worse outcome, indicating its complex role in RCC pathogenesis. In blood serum, piR-823 is up-regulated, but with unsatisfactory analytical performance. Preliminary data indicate the promising diagnostic utility of urinary piR-823 in patients with RCC.
Keywords: nádory ledvin; Humans; lidé středního věku; Biomarkers, Tumor; Aged; mladý dospělý; dospělí; Area Under Curve; piR-823; senioři; lidé; renal cell carcinoma; tumor tissue; RNA, Small Interfering; nádorové biomarkery; Adult; malá interferující RNA; Middle Aged; Aged, 80 and over; karcinom z renálních buněk; Young Adult; plocha pod křivkou; senioři nad 80 let; Carcinoma, Renal Cell; blood serum; urine; PIWI-interacting RNA; Kidney Neoplasms